2018
DOI: 10.1039/c8ee00001h
|View full text |Cite
|
Sign up to set email alerts
|

Single-particle measurements of electrochemical kinetics in NMC and NCA cathodes for Li-ion batteries

Abstract: aThe electrochemical kinetics of battery electrodes at the single-particle scale are measured as a function of state-of-charge, and interpreted with the aid of concurrent transmission X-ray microscopy (TXM) of the evolving particle microstructure. An electrochemical cell operating with near-picoampere current resolution is used to characterize single secondary particles of two widely-used cathode compounds, NMC333 and NCA. Interfacial charge transfer kinetics are found to vary by two orders of magnitude with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
229
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 267 publications
(259 citation statements)
references
References 47 publications
14
229
2
Order By: Relevance
“…As shown in Supplementary Fig. 2a, the three-dimensional (3D) rendering and the virtual xy-slice through the center of the particle highlight the mesoscale morphological defects that are formed upon electrochemical cycling prior to any thermal treatments [21][22][23][24][25] . We present the morphological comparison between the initial state at room temperature and the state after the particle was exposed to the mildly elevated temperature at ~100 o C for ~5 hours.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Supplementary Fig. 2a, the three-dimensional (3D) rendering and the virtual xy-slice through the center of the particle highlight the mesoscale morphological defects that are formed upon electrochemical cycling prior to any thermal treatments [21][22][23][24][25] . We present the morphological comparison between the initial state at room temperature and the state after the particle was exposed to the mildly elevated temperature at ~100 o C for ~5 hours.…”
Section: Resultsmentioning
confidence: 99%
“…b) Transmission X‐ray microscopy tomograms showing slices at their midpoints of individual particles of the NCM333 and NCA after charging at C/3 rate to 3.9, 4.1, and 4.5 V, respectively. Reproduced with permission . Copyright 2018, Royal Society of Chemistry.…”
Section: Origins Of Surface/interface Structure Degradationmentioning
confidence: 99%
“…Very recently, it has been shown that by understanding the functional form of the reaction rate expressions, one is able to control, and consequently engineer, the physics of interfaces where reactions take place [26]. Representative examples are the lithiation of LFP and LiNi 1/3 Mn 1/3 Co 1/3 O 2 [149,150] particles, as well as the operation of Li-air batteries, where the thermodynamic stability of the system is controlled by varying the applied current [13,95,102,151,152]. In terms of CIET, by understanding the concentration dependencies of both the reorganization energy and the density of states of the electron donor, we will be able to control interface structure by inducing or suppressing phase separation/island formation.…”
Section: Discussionmentioning
confidence: 99%